Technology Augmented Reality Integration Hydrometeorology (TARIH) as Media Solution in Disaster Management for Physics Teacher Candidate - Wibowo, Firmanul Catur; Sanjaya, Lari Andres; Darman, Dina Rahmi; Basyir, Syifa Nabila; Gregersen, Andrea Fransiska Møller (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to develop Augmented Reality Integration Hydrometereology (TARIH) technology as a learning media solution for disaster management from an early warning to the effects of land subsidence. The research method used in this study is the Model ADDIE (Analysis, Design, Develop, Implement, and Evaluate). The chosen subjects of the current study were 69 physics teacher candidates aged 21-23 years at a university in Jakarta and Banten, Indonesia. Based on reliability tests obtained in this line of research, the findings disclosed that the response to the application of TARIH as media in hydrometereology learning, the reliability of the System Quality aspect was 0.69 and the mean was 4.43. Most importantly, the reliability of the information quality aspect was 0.43 and the mean was 4.39 and the reliability of the service quality aspect was 0.74 and the mean was 4.45. Based on results obtained in this line of research, the study indicated that TARIH media can be used as a learning media solution in Disaster Management from an early warning.Keywords: technology augmented reality integration hydrometeorology (TARIH), learning media, disaster learning media, physics teacher candidate.